Предмет: Алгебра,
автор: алина935
Помогите пожалуйста решить уравнение:
Приложения:
Ответы
Автор ответа:
0
х(х+1)^2-2(x+1)=0
(x+1)((x(x+1)-2))=0
(x+1)(x^2+x-2)=0
x+1= 0 или x^2+x-2=0
x=-1 по теореме виетта
x1=-2, х2=1
(x+1)((x(x+1)-2))=0
(x+1)(x^2+x-2)=0
x+1= 0 или x^2+x-2=0
x=-1 по теореме виетта
x1=-2, х2=1
Похожие вопросы
Предмет: Русский язык,
автор: 20dokidoki06
Предмет: Математика,
автор: egorantkon
Предмет: Английский язык,
автор: bakzhand
Предмет: Геометрия,
автор: Помидорка1309
Предмет: История,
автор: полинкапап